The Study of Academic Administrations for Developing English Learning Achievement in the Ordinary National Educational Test (O-Net) of Primary 6 Students of Schools Under the Phichit Primary Educational Service Area Office 1 - Jaidee , Puttitaporn; Uppamaiathichai, Thirasak (Journal of Modern Learning Development, 2023)
The objective of this research was to study the guidelines of academic administration for developing English learning achievement in Ordinary National Educational Test (O-NET) of primary 6 students of schools under the Phichit Primary Educational Service Area Office 1. The results of the study for the guidelines of academic administration for developing English learning achievement in Ordinary National Educational Test (O-NET) of primary 6 students of schools under the Phichit Primary Educational Service Area Office 1 found that Administrators should determine the school curriculum in line with Ordinary National Educational Test (O-NET). Administrators promote teachers to teach in Active learning. Learning outcomes are measured and evaluated according to standards and indicators. Determine Quality Assurance per the certification standards specified by the government with the process of PLC. Administrators promote and support teachers to use media and technologies in teaching English to improve English learning achievement.